Impactos das mudanças de gestão das equipes de manutenção na eficiência e produtividade numa fábrica de malte: estudo de caso da implantação de novo formato de hierarquia e alterações da gestão de manutenção - Oliveira, Guilherme Centenaro de (Universidade do Vale do Rio dos Sinos, 2021)
Currently, maintenance can be an economic differential, because from the application applied in its management and execution, bigger and better results can be achieved. As an objective, this research will show the improvement achieved in the results of a manufacturing unit, from the change implemented in the hierarchical structure and maintenance strategies. From the program called the Maintenance Committee, which is based on total productive maintenance (TPM) and changes in teams, new practices were observed, data were collected and it was found that, as improvements implemented in the processes, they impacted the quality and costs of production. This research can contribute to future studies in the management of production and maintenance teams, in applied maintenance objectives and in the creation of a new method that links strategic management of people and maintenance.
Keywords: Estratégia; Custos; Qualidade; MPT; Strategy; Costs; Quality; TPM